Limitation of tax liabilities - Janas, Dominika (Journal of Finance and Financial Law, 2019)
Limitation of tax liabilities is ineffective form of the expiry of tax liability. The article deals with the issues of liability and prescription and its time limits, as well as the concepts of suspension and interruption of the limitation period. The effects and, what is more, data showing the amount of tax arrears in Poland in the years 2014–2017 were presented. The consequence of the statute of limitation is the inability to collect payment by the tax authority and the arrears of tax arrears affecting the state budget.